Analisis Fluktuasi Keuntungan Mitra Bisnis Franchise Ayam Geprek Sa'i dengan Sistem Persentase: Pendekatan dari Aspek Manajemen Pemasaran Syariah - Moh. Agus Sifa'; Moch. Zaenal Azis Muctharom (Journal of Islamic Banking, 2023)
ABSTRACT This research focuses on analyzing the process of purchasing a cooperation license and the implementation of the mudarabah agreement in the fluctuation of profit sharing between Geprek Sa'i franchisers and business partners. In purchasing the Ayam Geprek Sa'i franchise business license, the business partner includes initial capital of IDR. 350,000,000, including renovation of premises, equipment, supplies and use of the name Ayam Geprek Sa'i license. The mudarabah agreement is implemented with this initial capital, and the distribution of profits is carried out based on revenue sharing. In this system, 70% of the net profit income is given to the franchiser, while 30% is given to the business partner. This process is explained through ijab qabul, where the business partner can make an initial payment and provide a place, then confirm with the franchiser. Fluctuations in the Ayam Geprek Sa'i franchise business are influenced by location factors and raw material prices. The distribution of profits is based on net profit income for one month, and the distribution percentage refers to revenue sharing, namely 70% for franchisers and 30% for business partners. This research takes a qualitative descriptive approach to explain the process and application of mudarabah contracts in the context of sharia economic law.